2016
DOI: 10.1007/s11695-016-2361-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Bariatric and Metabolic Surgery in Japan: Results of a Multi-Institutional Survey

Abstract: Bariatric and metabolic surgery for Japanese morbidly obese patients is safe and effective. These results are comparable with the results of previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 26 publications
6
35
0
2
Order By: Relevance
“…Consistent with other studies, our results reflect significant improvements in the anthropometric variables in obese patients after LSG [5][6][7][8][9][10][11][12]. Moreover, our study confirms that LSG induced a substantial improvement in several glucose parameters.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies, our results reflect significant improvements in the anthropometric variables in obese patients after LSG [5][6][7][8][9][10][11][12]. Moreover, our study confirms that LSG induced a substantial improvement in several glucose parameters.…”
Section: Discussionsupporting
confidence: 92%
“…The criteria for remission and improvement in selected comorbidities were based on a previous study [8]. Complete remission included fasting glucose <100 mg/dL and HbA1c <6% without the use of medication for diabetes.…”
Section: Criteria For Remission and Improvement In T2dmmentioning
confidence: 99%
“…Our study found mean %TWL of 29.9% and diabetes CR of 75.6% at 2 years after surgery, together with high remission rates of other metabolic diseases. These findings are consistent with the results of a previous Japanese multi‐institutional survey …”
Section: Discussionmentioning
confidence: 99%
“…[13]. Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) are currently the most commonly performed bariatric surgeries with the latter rapidly gaining in popularity (for example [4, 5]).…”
Section: Introductionmentioning
confidence: 99%